Women in Kurdistan-Iraq: issues, obstacles and enablers. Issue 7 (2nd October 2016) - Joly, Danièle; Bakawan, Adel
Abstract : This article explores women's situation in Kurdistan-Iraq. We examine key issues of concern to Kurdish women and the arenas which present enablers and obstacles to their action: the family and tradition; Islam and Muslim institutions; political parties and the state; civil society associations and non-governmental organisations. We look at recently promulgated laws on violence against women and on personal status. Our research is based on in-depth interviews, legal documents, grey literature and internet sources.